Long-term filter efficiency of mobile air purifiers in schools. Issue 2 (1st February 2023) - Granzin, Manuel; Richter, Sarah; Schrod, Jann; Schubert, Natalie; Curtius, Joachim
Abstract: The SARS-CoV-2 pandemic forced many restrictions upon the public, such as the closing of schools, affecting social development and education of children. Here we tested air purifiers with HEPA filters as a measure to reduce the infection risk via airborne transmission during classes. We evaluated the efficiency and long-term performance of three devices over six month of operation at two schools by monitoring the particle decay from 0.003 to 10 µm. We found that the particle concentration was reduced reliably and spatially homogenously by 85 − 95% throughout the whole observed particle spectrum within ∼20 min for air exchange rates between 4.8 and 6.7 h −1 . During the study we did not observe a clear decline in efficiency or performance of the air purifiers. We complemented our particle measurements with model calculations to estimate the virus concentration and inhaled dose of a susceptible person, assuming one infectious person was present. We calculated that the additional use of air purifiers reduced the number of potentially inhaled viruses at the end of the day by a factor of 2.65 relative to the case without air purifiers. Further, school-wide surveys indicated that the disturbance by the noise level of the air purifiers is to be considered and that the acceptance of air purifiers can be improved when the noise level is reduced. Overall, our study suggests that a combination of air purifiers and venting is a well-suited measure to reduce the potential indoor viral-load while still introducing fresh air into the room.